Pembelajaran Inovatif Abad 21 pada Materi Deskriptif Teks dengan Model Pembelajaran Problem Based Learning di SMK Negeri 1 Adiwerna - Imron, Imron (Universitas Pancasakti Tegal, 2022)
The 21st century educational paradigm has experienced a shift marked by differences in learning orientation. Innovative learning in the 21st century is activity-oriented to train essential skills according to the framework for 21st century skills, namely life and career skills, innovation and learning skills, and information, media, and ICT skills. This research method is using a qualitative descriptive method. While the research instruments used were document notes and interviews in the form of 3 lesson plans made by the English teacher. This study aims to determine the suitability of the English Learning Implementation Plan (RPP) on “descriptive text” material at SMK Negeri 1 Adiwerna based on 3 learning models that are suitable for 21st century learning, namely the learning model of Discovery, Inquiry and Problem Based Learning. The aspect studied is the preparation of the learning steps of the 3 models. The results of the data collected by paying attention to the preparation instructions showed that the RPP with the Problem Based Learning (PBL) learning model, it was known that the RPP was not in accordance with 21st century learning steps.